2018
DOI: 10.1093/ajae/aay023
|View full text |Cite
|
Sign up to set email alerts
|

A Century of U.S. Farm Productivity Growth: A Surge Then a Slowdown

Abstract: U.S. farm productivity growth has direct consequences for sustainably feeding the world's still rapidly growing population, as well as U.S. competitiveness in international markets. Using a newly expanded compilation of multifactor productivity (MFP) estimates and associated partial‐factor productivity (PFP) measures, we examine changes in the pattern of U.S. agricultural productivity growth over the past century and more. Considering the evidence as a whole, we detect sizable and significant slowdowns in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 20 publications
0
15
1
1
Order By: Relevance
“…Interestingly, our posterior mean estimates of productivity growth in the farm production from Model I are notably greater than those reported earlier by Ball et al (1997) and more recently by Andersen, Alston, Pardey & Smith (2018) and Plastina & Lence (2018). This may be plausibly attributed to distinct differences in the productivity measurement methodologies.…”
Section: Variablescontrasting
confidence: 67%
“…Interestingly, our posterior mean estimates of productivity growth in the farm production from Model I are notably greater than those reported earlier by Ball et al (1997) and more recently by Andersen, Alston, Pardey & Smith (2018) and Plastina & Lence (2018). This may be plausibly attributed to distinct differences in the productivity measurement methodologies.…”
Section: Variablescontrasting
confidence: 67%
“…twentieth century an anomaly in a sector characterized by slow productivity growth. Ball, Schimmelpfennig, and Wang (2013), Alston (2018), and Andersen et al (2018) provide comprehensive discussions about the competing hypotheses behind the slowdown in U.S. agricultural productivity.…”
Section: Productivity Gainsmentioning
confidence: 99%
“…As well, the World Health Organization's International Agency for Research on Cancer also concluded that the presence of glyphosate in drinking water does not represent a hazard to human health (WHO, 2017). 4 There is mixed and sometimes competing evidence regarding agricultural productivity growth in the world, with the predominant result that agricultural productivity growth has slowed, especially in the world's richest countries (for details see, Andersen, Alston, Pardey, & Smith, 2018;Darku, Malla, & Tran, 2016). (especially with the Tobin and Westar varieties).…”
Section: Overviewmentioning
confidence: 99%
“…The global population is expected to increase significantly in the next few decades. At the same time, global agricultural productivity growth has slowed down, especially in the world's richest countries (Andersen, Alston, Pardey, & Smith, ). This trend has been mainly attributed to underinvestment in certain types of productivity enhancing agricultural R&D (Alston, Beddow, & Pardey, ; Alston, James, Andersen, & Pardey, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation